Introduction to the Special Issue on the 2006 IEEE International Solid-State Circuits Conference. - Warnock, J. D.
The 24 papers in this special issue are among those that were presented at the 2006 IEEE International Solid-State Circuits Conference in February 2006. The papers come from the following sessions: Digital; Technology Directions; Signal Processing; and Memory. Briefly summarizes the articles included in this issue.